ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT WAJIB PAJAK ORANG PRIBADI DALAM MENGGUNAKAN E-FILING SEBAGAI SARANA PELAPORAN SPT PADA KPP PRATAMA POSO - Sondakh, Jullie J.; Budiarso, Novi S.; Pu’o, Sofyarifani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The purpose of this research is to examine the factors affecting interests of taxpayers in using e-Filing facility. The dependent variable used in this research is the interest of tax payers, while the independent variables are perceived usefulness, perceived ease of use, security and privacy, complexity, and readiness technology taxpayers information. The respondents are individual taxpayers who used e-Filing that are listed in Poso, Tax Office. This research used multiple linear regression analysis that involved 100 respondents. The results show that: (1) perceived usefulness affects positively the intention to use e-Filing, (2) perceived ease of use affects positively the intention to use e-Filing, (3) security and privacy affects positively the intention to use e-Filing, (4) complexity affects negatively the intention to use e-Filing, (5) readiness technology taxpayers information affects positively the intention to use e-Filing. Keywords: Perceived Usefulness, Perceived Ease Of Use, Security and Privacy, Complexity, Readiness Technology Taxpayers Information, e-Filing.